Morphology, distribution and abundance of antennal sensilla of the oyster mushroom fly, Coboldia fuscipes (Meigen) (Diptera: Scatopsidae) - Zhilin Zhang; Xinlian Li; Lizhen Chen; Lihua Wang; Chaoliang Lei (Revista Brasileira de Entomologia, 2016)
ABSTRACT We investigated the distribution, morphology and abundance of antennae sensilla of Coboldia fuscipes (Meigen) using scanning electron microscopy. Antennae of C. fuscipes consisted of scape, pedicel, and flagellum with eight flagellomeres. Antennal scape and pedicel had only one type of sensillum, i.e., sensilla chaetica. Significant differences were found between the number and distribution of these sensilla. Four types of morphologically distinct sensilla on the flagellum were identified, including sensilla chaetica, sensilla trichoidea, sensilla coeloconica, and sensilla basiconica (three subtypes). Significant differences were found in the abundance and distribution of sensilla among the antennal flagella and diverse flagellomeres in both sexes. Sensilla trichoidea is the most abundant of sensilla discovered on the antennal flagellum. Sensilla chaetica is the largest and longest sensilla among all the types of sensilla found on the antennal surface of C. fuscipes. Sensilla coeloconica is widely distributed all over the flagellum surface except for the first of female. Some significant differences in the abundance and distribution were also observed among sensilla basiconica of flagellum. The probable biological function of each sensillum type was deduced based on the basis of their structure. These results serve as important basis for further studies on the host location mechanism and mating behavior of C. fuscipes.